A CRITICAL DISCOURSE ANALYSIS ON LGBT ON REPUBLIKA ONLINE NEWS ARTICLES - Elis Prastiwi (Department of Master of Linguistic, Universitas Airlangga, 2021)
The position of LGBT in Indonesia has received a vague response recently. There are also many marginalization and stereotypes faced by this community in Indonesia despite some acceptances received. This study will examine the stereotype of LGBT reflected within news articles. Employing socio-cognitive approach by Van Dijk (as cited in Wodak and Meyer, 2001), the researcher aims to: (1) find out the lexical choices found in Republika Online (ROL) news articles that contain stereotype towards LGBT Community, (2) discover Indonesian cognition depicted in the news articles, and (3) find out readers' responses to the stereotype addressed to LGBT community. The researcher conducted qualitative research to elaborate on the findings of stereotypes found in ROL. The data were obtained from a document analysis to find out the discourse and cognition level, and an interview to search the society level. The researcher found that stereotypes “LGBT is an illness” and “LGBT is a threat to the nation”s in ROL have represented LGBT. These stereotypes were motivated by the rejection of LGBT's existence, a shift in attitude toward LGBT, and ROL Muslim ideology. From the interview, the readers showed various responses toward the news; agreement to the stereotype by a reader, and disagreement by three others due to various reasons. In conclusion, the stereotypes of LGBT in ROL have caused negative images of this community even though they were not supported by scientific explanation in the ROL. The readers however have reacted towards these stereotypes differently, regardless of the negative images caused by the ROL stereotypes towards the LGBT community.